ANALISIS PRAKTIK MONOPOLI DALAM PEMASARAN BAHAN BAKAR AVTUR DI INDONESIA DARI PERSPEKTIF HUKUM PERSAINGAN USAHA: Analysis Of Monopolistic Practices In Marketing Avtural Fuel In Indonesia From A Competition Law Perspective - Razaan Nazhif Firmansyah; A.M Tri Anggraini (Faculty of Law, Universitas Trisakti, 2024)
Competition in the aviation sector is crucial for improving quality of life and the economy. The formulation of the problem of this article is the form of government policy in the marketing of avtur fuel by PT Pertamina Patra Niaga which results in monopolistic practices and unfair business competition, and the potential exemption of PT Pertamina Patra Niaga from Articles 50(a) and 51 of Law No. 5 of 1999. Using a normative legal method with a legislative approach and descriptive nature, secondary data was obtained through literature studies and interviews with the Federation of United Pertamina Workers' Union (FSPBB). The research results and conclusions are government policies in avtur marketing by PT Pertamina Patra Niaga have created a natural monopoly harming consumers and hindering healthy competition, and exemption from Article 50(a) of Law No. 5/1999 is justified, but PT Pertamina Patra Niaga does not meet Article 51 criteria as it is not a state-owned enterprise but a subsidiary of PT Pertamina Persero.